The production of the rail system. Towards a historical IDE of rail heritage of Andalusia - Patricia Ferreira Lopes (Virtual Archaeology Review)
The railway process (1854-1940) in Andalucia contributed to the formation of a new territorial structure. The railway, built and used, was also a means of production: business networks, flows of raw materials and people, energy technologies that shaped the land and also were shaped by it. In this sense, the railroad, produced and producer of various changes, cannot be understood without its productive forces, including knowledge and technology, the working class, the superstructure of society, the State and nether can't be separated from nature, where the topography and hydrology played important role. These factors are combined, juxtaposed, are interspersed, engage and sometimes collide, creating what might be called the " rail rhizome", a hyper complex space, intervened and shaped by a diversity of actors. This paper presents a new interpretation of the Andalucia railway heritage through the application of a Geographic Information System (GIS), which based on the historical creation of a spatial data infrastructure (SDI) of railways in Andalucia, open and expands its spatiotemporal vision.